A high-performance lithium iron manganese phosphate composite material, a preparation method thereof and application thereof
Patent Information
- Application Number
- CN202410070416.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-17
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-01-17
AI Technical Summary
采用传统方法能够一定程度上提高磷酸锰铁锂复合材料的压实性能,但会导致材料的容量性能明显衰减,由此可见,提高磷酸锰铁锂复合材料的压实性能并兼顾其容量性能是磷酸锰铁锂目前迫切需要解决的技术问题
[0044] 1. This invention improves the lithium-ion diffusion rate by doping with aluminum, thereby enhancing the capacity performance of lithium manganese iron phosphate composite materials.
Smart Images

Figure CN117936736B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery material technology, specifically relating to a high-performance lithium manganese iron phosphate composite material, its preparation method, and its application. Background Technology
[0002] Lithium iron phosphate (LiFePO4) is a widely used cathode material for power batteries, favored by the electric vehicle market due to its good safety and long cycle life. However, it has a relatively low operating voltage. 3+ / Fe 2+ Compared to Li + The potential of / Li is only 3.4V, which results in low specific energy of lithium iron phosphate materials, thus limiting their development to some extent.
[0003] Lithium manganese phosphate has a similar structure to lithium iron phosphate materials, and it has a higher operating voltage. 3+ / Fe 2+ Compared to Li + The potential of / Li is 4.1V, which makes the specific energy of lithium manganese phosphate materials relatively high. However, the poor conductivity of lithium manganese phosphate limits its development and application.
[0004] Lithium manganese iron phosphate combines the advantages of the two materials mentioned above, possessing both 4V-level capacity and good conductivity. Due to its high specific energy and other advantages, it is becoming a potential material for next-generation power batteries.
[0005] The main challenges currently facing lithium manganese iron phosphate (LFP) composite materials are: compared to lithium iron phosphate (LFP), LFP composite materials exhibit significantly lower compaction performance and lower capacity performance. While traditional methods can improve the compaction performance of LFP composite materials to some extent, this leads to a significant decrease in capacity performance. Therefore, improving the compaction performance of LFP composite materials while maintaining their capacity performance is a pressing technical problem that needs to be solved. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a high-performance lithium manganese iron phosphate composite material. This method improves the capacity performance of the lithium manganese iron phosphate composite material and reduces the carbon content by adding aluminum ions and zirconium nitride. In addition, the specific process also improves the compaction performance of the lithium manganese iron phosphate composite material.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] In a first aspect, the present invention provides a lithium manganese iron phosphate composite material, which comprises the following components: lithium manganese iron phosphate material and a coating layer on its surface;
[0009] The coating layer is formed of carbon and zirconium nitride;
[0010] In the lithium manganese iron phosphate material, the molar ratio of Li:Mn:Fe:P is (1-1.03):x:(1-x):1, where x takes a value of 0.5-0.7; specifically, x can take values of 0.5-0.6, 0.6-0.7, 0.5-0.55, 0.55-0.65, 0.6, and 0.7.
[0011] The lithium manganese iron phosphate material is also doped with aluminum ions.
[0012] The molar ratio of zirconium ions to nitrogen ions in the zirconium nitride is 1:(1-2); such as 1:(1-1.5), 1:1, or 1:2.
[0013] The molar ratio of zirconium ions to iron ions in the lithium manganese iron phosphate composite material is (0.001-0.005):1, such as (0.001-0.002):1, (0.001-0.003):1, (0.001-0.004):1, (0.001-0.0035):1, 0.001:1, 0.005:1.
[0014] The molar ratio of aluminum ions to manganese ions in the lithium manganese iron phosphate composite material is (0.001-0.005):1, such as (0.001-0.002):1, (0.001-0.003):1, (0.001-0.004):1, (0.001-0.0035):1, 0.001:1, 0.005:1.
[0015] The carbon content in the lithium manganese iron phosphate composite material is 1.2-1.4%, such as 1.2-1.3%, 1.3-1.4%, 1.2% or 1.4%.
[0016] The particle size D of the lithium manganese iron phosphate composite material 50 0.8-1.5μm, such as 0.8-1μm, 1.0-1.2μm, 1.2-1.5μm, 0.8μm, 1.0μm, 1.2μm or 1.5μm, D 100 ≤7μm.
[0017] Secondly, the present invention provides a method for preparing the above-mentioned lithium manganese iron phosphate composite material, comprising the following steps:
[0018] S1. Iron source, phosphorus source, lithium source, manganese source, aluminum-containing additive A, carbon source and deionized water are mixed to obtain slurry A, which is then sintered to obtain carbon-coated lithium manganese iron phosphate sample A.
[0019] S2. Mix the lithium manganese iron phosphate sample A, deionized water, soluble zirconium-containing additive B, soluble nitrogen-containing additive C, and carbon source to obtain slurry B;
[0020] S3. Spray dry the slurry B under grinding conditions and sinter it to obtain the lithium manganese iron phosphate composite material.
[0021] In step S1, the iron source is one or more of iron oxide, iron nitrate, and iron phosphate.
[0022] In step S1, the phosphorus source is one or more of ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and iron phosphate.
[0023] In step S1, the lithium source is one or more of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate.
[0024] In step S1, the manganese source is one or more of manganese trioxide, manganese tetroxide, and manganese carbonate.
[0025] In step S1, the aluminum-containing additive A is one or more of aluminum oxide, aluminum nitrate, and aluminum carbonate.
[0026] In step S1, the carbon source is one or more of glucose, starch, and polyethylene glycol-1500 (PEG-1500).
[0027] In step S1, the mixing conditions are as follows: the rotation speed is 200-400 r / min, such as 200-300 r / min, 300-400 r / min, 250-350 r / min, 200 r / min, 300 r / min, and the mixing time is 1-3 h, such as 1-2 h, 2-3 h, 1.5-2.5 h, 2 h, 3 h.
[0028] In step S1, the solid content of the slurry A is 35%-45%wt, such as 35%-40%wt, 40%-45%wt, 35%wt or 45%wt.
[0029] In step S1, the slurry A is wet-milled, spray-dried, and sintered to obtain the carbon-coated lithium manganese iron phosphate A sample;
[0030] In step S1, the slurry A is wet-milled to a particle size D. 50 The range is 0.5-0.6μm, such as 0.5-0.55μm, 0.55-0.6μm, 0.55μm, and 0.6μm.
[0031] In step S1, the conditions for spray drying are: the inlet air temperature is 200-260℃, such as 200-220℃, 220-240℃, 240-260℃, 200℃ or 260℃, and the outlet air temperature is 100-110℃, such as 100-105℃, 105-110℃, 100℃ or 110℃.
[0032] In step S1, the sintering procedure is as follows: first, the temperature is raised to 200-250℃, such as 200-225℃, 225-250℃, 200℃, or 250℃; then, the temperature is raised to 400-500℃, such as 400-450℃, 450-500℃, 400℃, or 500℃; the sintering time is 3-5 hours, such as 3-4 hours, 4-5 hours, 3 hours, or 5 hours. The heating rate is 3-5℃ / min, such as 3-4℃ / min, 4-5℃ / min, 3℃ / min, or 5℃ / min.
[0033] In step S1, the carbon content in the lithium manganese iron phosphate sample A is 0.3-0.5%, such as 0.3-0.4%, 0.4-0.5%, 0.3% or 0.5%.
[0034] In step S2, the soluble zirconium-containing additive B is zirconium tetrachloride or zirconium nitrate.
[0035] In step S2, the soluble nitrogen-containing additive C is urea or ammonia.
[0036] In step S3, the mixing conditions are as follows: the rotation speed is 200-400 r / min, such as 200-300 r / min, 300-400 r / min, 250-350 r / min, 200 r / min, 300 r / min, and the mixing time is 1-3 h, such as 1-2 h, 2-3 h, 1.5-2.5 h, 2 h, 3 h.
[0037] In step S3, the solid content in the slurry B is 35%-45%wt, such as 35%-40%wt, 40%-45%wt, 35%wt or 45%wt.
[0038] In step S3, the slurry B is ground to a particle size of 0.5-0.6 μm, such as 0.5-0.55 μm, 0.55-0.6 μm, 0.5 μm or 0.6 μm.
[0039] In step S3, the conditions for spray drying are: the inlet air temperature is 200-260℃, such as 200-220℃, 220-240℃, 240-260℃, 200℃ or 260℃, and the outlet air temperature is 100-110℃, such as 100-105℃, 105-110℃, 100℃ or 110℃.
[0040] In step S3, after the spray drying is completed, the particle size D of the material is... 50 The range is 0.4-0.45μm, such as 0.4-0.425μm, 0.425μm-4.5μm, 0.4μm, or 0.45μm.
[0041] In step S3, the sintering procedure is as follows: first, the temperature is raised to 300-350℃, such as 300-325℃, 325-350℃, 300℃ or 350℃, and then raised to 750-780℃, 750-760℃, 760-770℃, 770-780℃, 750℃, 770℃ or 780℃, and the sintering time is 6-8h, such as 6-7h, 7-8h, 6h or 8h; wherein, the heating rate is 3-5℃ / min, such as 3-4℃ / min, 4-5℃ / min, 3℃ / min or 5℃ / min.
[0042] Thirdly, the present invention further provides a lithium-ion battery, comprising a positive electrode and a negative electrode; wherein the material of the positive electrode is the aforementioned lithium manganese iron phosphate composite material.
[0043] The beneficial effects achieved by this invention are as follows:
[0044] 1. This invention improves the lithium-ion diffusion rate by doping with aluminum, thereby enhancing the capacity performance of lithium manganese iron phosphate composite materials.
[0045] 2. This invention adds zirconium ions and nitrogen ions to form superconducting zirconium nitride under high temperature conditions. This zirconium nitride is coated on the surface of lithium manganese iron phosphate material, which improves the electronic conductivity of the material and reduces the amount of carbon coating, thereby improving the compaction performance of the material.
[0046] 3. This invention creatively adopts a side-sand grinding and spraying process, which gives the finished lithium manganese iron phosphate particles a better particle size distribution effect, thereby improving the compaction performance of the material.
[0047] 4. The method and process provided by this invention are relatively simple, easy to operate, highly repeatable, require less equipment, and produce materials with stable performance. Attached Figure Description
[0048] Figure 1 SEM characterization of the lithium manganese iron phosphate composite material prepared in Example 4.
[0049] Figure 2 SEM characterization of the lithium manganese iron phosphate composite material prepared in Comparative Example 6. Detailed Implementation
[0050] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.
[0051] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0052] Unless otherwise specified, all reagents, materials, instruments, etc. used in the following examples are commercially available.
[0053] Example 1
[0054] The steps are as follows:
[0055] S1. Iron oxide, lithium dihydrogen phosphate, manganese trioxide, lithium carbonate, and glucose are mixed with deionized water in an elemental molar ratio of Li:Mn:Fe:P = 1.01:0.5:0.5:1 to obtain slurry A. Alumina is then added at a ratio of Al:Mn = 0.001:1. The mixture is stirred at 200 r / min for 1 h to obtain slurry A.
[0056] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.5μm. Spray it with an inlet air temperature of 200℃ and an outlet air temperature of 100℃. After completion, heat it to 200℃ at 3℃ / min under a nitrogen atmosphere, hold it for 1h, then heat it to 400℃ and hold it for 3h to complete sintering and obtain lithium manganese iron phosphate A sample with a carbon content of 0.3%.
[0057] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water, zirconium tetrachloride, urea and glucose are mixed with a solid content of 35%. The amount of zirconium tetrachloride added is such that the molar ratio of zirconium ions to iron ions is Zr:Fe = 0.001:1, and the amount of urea added is such that the molar ratio of zirconium ions to nitrogen ions is Zr:N = 1:1. After mixing, the mixture is stirred at 200 r / min for 1 h. After completion, slurry B is obtained.
[0058] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.5 μm, continue grinding and start spraying with an inlet air temperature of 200℃ and an outlet air temperature of 100℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.4 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 350℃ at 3℃ / min, hold for 1 hour, raise the temperature to 730℃, hold for 6 hours. After sintering, perform air jet milling to obtain a finished product of lithium manganese iron phosphate with a particle size of D50 = 0.8 μm and a carbon content of 1.2%.
[0059] Example 2
[0060] The steps are as follows:
[0061] S1. Ferric nitrate, ammonium dihydrogen phosphate, manganese tetroxide, lithium hydroxide, and PEG-1500 are mixed with deionized water at an elemental molar ratio of Li:Mn:Fe:P = 1.03:0.7:0.3:1, with a solid content of 45%. Then aluminum nitrate is added at an aluminum ion to manganese ion ratio of Al:Mn = 0.005:1. The mixture is then stirred at 400 r / min for 3 h to obtain slurry A.
[0062] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.6μm. Spray it with an inlet air temperature of 260℃ and an outlet air temperature of 110℃. After completion, heat it to 250℃ at 5℃ / min under a nitrogen atmosphere, hold it for 2h, then heat it to 500℃ and hold it for 5h to complete sintering and obtain lithium manganese iron phosphate A sample with a carbon content of 0.5%.
[0063] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water, zirconium nitrate, ammonia, and PEG-1500 were mixed with a solid content of 45%. The amount of zirconium nitrate added was such that the molar ratio of zirconium ions to iron ions was Zr:Fe = 0.005:1, and the amount of ammonia added was such that the molar ratio of zirconium ions to nitrogen ions was Zr:N = 1:2. After mixing, the mixture was stirred at 400 r / min for 3 h. After the mixture was completed, slurry B was obtained.
[0064] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.6 μm, continue grinding and start spraying at an inlet air temperature of 260℃ and an outlet air temperature of 110℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.45 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 400℃ at 5℃ / min, hold for 2 hours, raise the temperature to 780℃, hold for 8 hours. After sintering, perform air jet milling to obtain a finished product of lithium manganese iron phosphate with a particle size of D50 = 1.5 μm and a carbon content of 1.4%.
[0065] Example 3
[0066] The steps are as follows:
[0067] S1. Iron phosphate, lithium dihydrogen phosphate, manganese carbonate, lithium carbonate, and starch are mixed with deionized water in an elemental molar ratio of Li:Mn:Fe:P = 1.02:0.6:0.4:1, with a solid content of 40%. Then aluminum carbonate is added at an aluminum ion to manganese ion ratio of Al:Mn = 0.003:1. The mixture is stirred at 300 r / min for 2 h to obtain slurry A.
[0068] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.55μm. Spray it with an inlet air temperature of 240℃ and an outlet air temperature of 105℃. After completion, heat it to 230℃ at 4℃ / min under a nitrogen atmosphere and hold it for 1.5h. Then heat it to 450℃ and hold it for 4h to complete sintering and obtain lithium manganese iron phosphate sample A with a carbon content of 0.4%.
[0069] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water, zirconium tetrachloride, ammonia water, and starch were mixed with a solid content of 40%. The amount of zirconium tetrachloride added was such that the molar ratio of zirconium ions to iron ions was Zr:Fe = 0.003:1, and the amount of ammonia water added was such that the molar ratio of zirconium ions to nitrogen ions was Zr:N = 1:1.5. After mixing, the mixture was stirred at 300 r / min for 2 h to obtain slurry B.
[0070] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.55 μm, continue grinding and start spraying with an inlet air temperature of 240℃ and an outlet air temperature of 105℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.43 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 380℃ at 4℃ / min, hold for 1.5h, raise the temperature to 750℃, hold for 7h. After sintering, perform air jet milling to obtain the finished product of lithium manganese iron phosphate with a particle size of D50 = 1μm and a carbon content of 1.3%.
[0071] Example 4
[0072] The steps are as follows:
[0073] S1. Iron phosphate, lithium dihydrogen phosphate, manganese tetroxide, lithium carbonate, and PEG-1500 are mixed with deionized water at an elemental molar ratio of Li:Mn:Fe:P = 1.012:0.6:0.4:1, with a solid content of 35%. Then aluminum carbonate is added at an aluminum ion to manganese ion ratio of Al:Mn = 0.003:1. The mixture is then stirred at 400 r / min for 3 h to obtain slurry A.
[0074] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.6μm. Spray it with an inlet air temperature of 220℃ and an outlet air temperature of 100℃. After completion, heat it to 200℃ at 5℃ / min under a nitrogen atmosphere, hold it for 1 hour, then heat it to 450℃ and hold it for 3 hours to complete sintering and obtain lithium manganese iron phosphate A sample with a carbon content of 0.5%.
[0075] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water, zirconium nitrate, urea, and PEG-1500 were mixed with a solid content of 35%. The amount of zirconium nitrate added was such that the molar ratio of zirconium ions to iron ions was Zr:Fe = 0.003:1, and the amount of urea added was such that the molar ratio of zirconium ions to nitrogen ions was Zr:N = 1:1. After mixing, the mixture was stirred at 400 r / min for 3 h to obtain slurry B.
[0076] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.6 μm, continue grinding and start spraying with an inlet air temperature of 220℃ and an outlet air temperature of 100℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.4 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 400℃ at 5℃ / min, hold for 1 hour, raise the temperature to 750℃, hold for 8 hours. After sintering, perform air jet milling to obtain the finished product of lithium manganese iron phosphate with a particle size of D50 = 1 μm and a carbon content of 1.4%.
[0077] Comparative Example 1
[0078] The steps are as follows:
[0079] S1. Iron oxide, lithium dihydrogen phosphate, manganese trioxide, lithium carbonate, and glucose are mixed with deionized water in an elemental molar ratio of Li:Mn:Fe:P = 1.01:0.5:0.5:1 to obtain slurry A. Alumina is then added at a ratio of Al:Mn = 0.001:1. The mixture is stirred at 200 r / min for 1 h to obtain slurry A.
[0080] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.5μm. Spray it with an inlet air temperature of 200℃ and an outlet air temperature of 100℃. After completion, heat it to 200℃ at 3℃ / min under a nitrogen atmosphere, hold it for 1 hour, then heat it to 400℃ and hold it for 3 hours to complete sintering and obtain lithium manganese iron phosphate A sample with a carbon content of 0.3%.
[0081] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water, titanium tetrachloride, boron oxide and glucose are mixed with a solid content of 35%. The amount of zirconium tetrachloride added is such that the molar ratio of zirconium ions to iron ions is Zr:Fe = 0.001:1, and the amount of urea added is such that the molar ratio of zirconium ions to nitrogen ions is Zr:N = 1:1. After mixing, the mixture is stirred at 200 r / min for 1 h to obtain slurry B.
[0082] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.5 μm, continue grinding and start spraying with an inlet air temperature of 200℃ and an outlet air temperature of 100℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.4 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 350℃ at 3℃ / min, hold for 1 hour, raise the temperature to 730℃, hold for 6 hours. After sintering, perform air jet milling to obtain a finished product of lithium manganese iron phosphate with a particle size of D50 = 0.8 μm and a carbon content of 1.2%.
[0083] Comparative Example 2
[0084] The steps are as follows:
[0085] S1. Ferric nitrate, ammonium dihydrogen phosphate, manganese tetroxide, lithium hydroxide, and PEG-1500 are mixed with deionized water at an elemental molar ratio of Li:Mn:Fe:P = 1.03:0.7:0.3:1 to achieve a solid content of 45%. The mixture is then stirred at 400 r / min for 3 hours to obtain slurry A.
[0086] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.6μm. Spray it with an inlet air temperature of 260℃ and an outlet air temperature of 110℃. After completion, heat it to 250℃ at 5℃ / min under a nitrogen atmosphere, hold it for 2h, then heat it to 500℃ and hold it for 5h to complete sintering and obtain lithium manganese iron phosphate A sample with a carbon content of 0.5%.
[0087] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water, zirconium nitrate, ammonia, and PEG-1500 were mixed with a solid content of 45%. The amount of zirconium nitrate added was such that the molar ratio of zirconium ions to iron ions was Zr:Fe = 0.005:1, and the amount of ammonia added was such that the molar ratio of zirconium ions to nitrogen ions was Zr:N = 1:2. After mixing, the mixture was stirred at 400 r / min for 3 h to obtain slurry B.
[0088] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.6 μm, continue grinding and start spraying at an inlet air temperature of 260℃ and an outlet air temperature of 110℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.45 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 400℃ at 5℃ / min, hold for 2 hours, raise the temperature to 780℃, hold for 8 hours. After sintering, perform air jet milling to obtain a finished product of lithium manganese iron phosphate with a particle size of D50 = 1.5 μm and a carbon content of 1.4%.
[0089] Comparative Example 3
[0090] The steps are as follows:
[0091] S1. Iron phosphate, lithium dihydrogen phosphate, manganese carbonate, lithium carbonate, and starch are mixed with deionized water in an elemental molar ratio of Li:Mn:Fe:P = 1.02:0.6:0.4:1, with a solid content of 40%. Then, alumina is added at a ratio of Al:Mn = 0.003:1. The mixture is stirred at 300 r / min for 2 hours to obtain slurry A.
[0092] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.55μm. Spray it with an inlet air temperature of 240℃ and an outlet air temperature of 105℃. After completion, heat it to 230℃ at 4℃ / min under a nitrogen atmosphere and hold it for 1.5h. Then heat it to 450℃ and hold it for 4h to complete sintering and obtain lithium manganese iron phosphate sample A with a carbon content of 0.4%.
[0093] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water and starch are mixed with a solid content of 40%. After mixing, the mixture is stirred at 300 r / min for 2 hours to obtain slurry B.
[0094] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.55 μm, continue grinding and start spraying with an inlet air temperature of 240℃ and an outlet air temperature of 105℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.43 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 380℃ at 4℃ / min, hold for 1.5h, raise the temperature to 750℃, hold for 7h. After sintering, perform air jet milling to obtain the finished product of lithium manganese iron phosphate with a particle size of D50 = 1μm and a carbon content of 1.3%.
[0095] Comparative Example 4
[0096] The steps are as follows:
[0097] S1. Iron phosphate, lithium dihydrogen phosphate, manganese tetroxide, lithium carbonate, and PEG-1500 are mixed with deionized water at an elemental molar ratio of Li:Mn:Fe:P = 1.012:0.6:0.4:1, with a solid content of 35%. Then aluminum carbonate is added at an aluminum ion to manganese ion ratio of Al:Mn = 0.003:1. The mixture is then stirred at 400 r / min for 3 h to obtain slurry A.
[0098] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.6μm. Spray it with an inlet air temperature of 220℃ and an outlet air temperature of 100℃. After completion, heat it to 200℃ at 5℃ / min under a nitrogen atmosphere, hold it for 1h, then heat it to 450℃ and hold it for 3h to complete sintering and obtain lithium manganese iron phosphate A sample with a carbon content of 1%.
[0099] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water, zirconium nitrate, urea, and PEG-1500 were mixed with a solid content of 35%. The amount of zirconium nitrate added was such that the molar ratio of zirconium ions to iron ions was Zr:Fe = 0.003:1, and the amount of urea added was such that the molar ratio of zirconium ions to nitrogen ions was Zr:N = 1:1. After mixing, the mixture was stirred at 400 r / min for 3 h to obtain slurry B.
[0100] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.6 μm, continue grinding and start spraying with an inlet air temperature of 220℃ and an outlet air temperature of 100℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.4 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 400℃ at 5℃ / min, hold for 1 hour, raise the temperature to 750℃, hold for 8 hours. After sintering, perform air jet milling to obtain the finished product of lithium manganese iron phosphate with a particle size of D50 = 1 μm and a carbon content of 2.0%.
[0101] Comparative Example 5
[0102] The steps are as follows:
[0103] S1. Iron phosphate, lithium dihydrogen phosphate, manganese tetroxide, lithium carbonate, and PEG-1500 are mixed with deionized water at an elemental molar ratio of Li:Mn:Fe:P = 1.012:0.6:0.4:1, with a solid content of 35%. Then aluminum carbonate is added at an aluminum ion to manganese ion ratio of Al:Mn = 0.003:1. The mixture is then stirred at 400 r / min for 3 h to obtain slurry A.
[0104] S2. Grind the slurry A obtained in S1. After sand grinding, the particle size D50 of the slurry is 0.6μm. Spray it with an inlet air temperature of 220℃ and an outlet air temperature of 100℃. After completion, heat it to 200℃ at 5℃ / min under a nitrogen atmosphere, hold it for 1 hour, then heat it to 450℃ and hold it for 3 hours to complete sintering and obtain lithium manganese iron phosphate A sample with a carbon content of 0.5%.
[0105] S3. The lithium manganese iron phosphate sample A obtained in S2, deionized water, zirconium nitrate, urea, and PEG-1500 were mixed with a solid content of 35%. The amount of zirconium nitrate added was such that the molar ratio of zirconium ions to iron ions was Zr:Fe = 0.003:1, and the amount of urea added was such that the molar ratio of zirconium ions to nitrogen ions was Zr:N = 1:1. After mixing, the mixture was stirred at 400 r / min for 3 h to obtain slurry B.
[0106] S4. Grind the B slurry obtained in S3. When the particle size reaches D50 = 0.6 μm, start spraying with an inlet air temperature of 220℃ and an outlet air temperature of 100℃. After spraying, sinter under nitrogen atmosphere by raising the temperature to 400℃ at 5℃ / min and holding for 1 hour, then raising the temperature to 750℃ and holding for 8 hours. After sintering, perform air jet milling to obtain a finished product of lithium manganese iron phosphate with a particle size of D50 = 1 μm and a carbon content of 1.4%.
[0107] Comparative Example 6
[0108] The steps are as follows:
[0109] S1. Iron phosphate, lithium dihydrogen phosphate, manganese tetroxide, lithium carbonate, and PEG-1500 are mixed with deionized water in an elemental molar ratio of Li:Mn:Fe:P = 1.012:0.6:0.4:1 to achieve a solid content of 35%. Then, aluminum carbonate, zirconium tetrachloride, and urea are added. The addition amounts are: aluminum ion to manganese ion ratio of Al:Mn = 0.003:1, zirconium ion to iron ion molar ratio of Ti:Fe = 0.003:1, and zirconium ion to nitrogen ion molar ratio of Zr:N = 1:1. The mixture is then stirred at 400 r / min for 3 h to obtain slurry A.
[0110] 4. Grind the slurry A obtained from S3. When the particle size reaches D50 = 0.6 μm, continue grinding and start spraying with an inlet air temperature of 220℃ and an outlet air temperature of 100℃. Control the sand mill spraying speed. When the slurry particle size reaches D50 = 0.4 μm, the slurry spraying is completed. Sinter under nitrogen atmosphere, raise the temperature to 400℃ at 5℃ / min, hold for 1 hour, raise the temperature to 750℃, hold for 8 hours. After sintering, perform air jet milling to obtain the finished product of lithium manganese iron phosphate with a particle size of D50 = 1 μm and a carbon content of 1.4%.
[0111] Effect verification
[0112] 1. Microstructure
[0113] Depend on Figure 1 , Figure 2 It can be seen that the surface of the composite material obtained in Example 4 is coated with a layer composed of carbon and zirconium nitride, while the surface of the composite material obtained in Comparative Example 6 is coated with only carbon.
[0114] 2. Button performance test
[0115] The button cell fabrication was carried out according to the following steps: The lithium manganese iron phosphate composite materials prepared in Examples 1-4 and Comparative Examples 1-6 were used as the positive electrode, and then combined with auxiliary materials to form button cells, and their button cell performance was analyzed. Except for the positive electrode material, all other auxiliary materials required for button cell fabrication were any commercially available auxiliary materials.
[0116] The testing equipment is the Blue Electric Test Cabinet.
[0117] Test steps: Charge to 4.5V at 0.2C current density to complete the first charge test; discharge to 2.0V at 0.2C current density to complete the first discharge test; divide the first charge capacity by the first discharge capacity to obtain the first charge / discharge efficiency; perform three charge / discharge cycles at 0.2C current density, charging voltage limit of 4.5V, and discharging voltage of 2.0V, and find the median value of the three discharge capacities as the 0.2C discharge capacity; perform 100 charge / discharge cycles at 1C current density, charging voltage limit of 4.5V, and discharging voltage of 2.0V, and find the median value of the first three discharge capacities as the 1C discharge capacity; divide the 100th discharge capacity by the first discharge capacity to obtain the capacity retention rate; completing the above steps completes the coin cell performance test.
[0118] 3. Material compaction test
[0119] Weigh 0.5 g of the lithium manganese iron phosphate composite material prepared in Examples 1-4 and Comparative Examples 1-6 respectively, place them in the tablet press mold, place them in the tablet press, apply a pressure of 5 MPa, hold the pressure for 30 seconds, and test their density after demolding to complete the material compaction performance test.
[0120] Table 1. Performance of materials prepared in each embodiment and comparative example.
[0121]
[0122] As can be seen from Table 1, compared with Comparative Examples 1-6, Examples 1-4 show good improvements in coin cell capacity performance, capacity retention rate, and compaction. In particular, the lithium manganese iron phosphate material prepared in Example 4 shows improvements in capacity, cycle life, and compaction compared with other examples and comparative examples.
[0123] Comparing the test results of Example 1 and Comparative Example 1, the material's cycle performance was significantly improved after selecting an appropriate ratio of manganese to iron.
[0124] Comparing the test results of Example 2 and Comparative Example 2, the capacity performance of the material was significantly improved after adding aluminum.
[0125] Comparing the test results of Example 3 and Comparative Example 3, the capacity performance of the material is well improved after adding zirconium and nitrogen to react and coat the material surface with zirconium nitride.
[0126] Comparing the test results of Example 4 and Comparative Example 4, it can be seen that by selecting an appropriate carbon content range, the compaction performance of the material reaches a better level.
[0127] Comparing the test results of Example 4 and Comparative Example 5, it can be seen that the compaction performance of the material is significantly improved after adding the process of simultaneous spraying and sand milling.
[0128] Comparing the test results of Example 4 and Comparative Example 5, the two-step sintering method shows a significant improvement in material capacity and cycle performance compared to the one-step sintering method.
[0129] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A lithium manganese iron phosphate composite material, comprising the following components: lithium manganese iron phosphate material and a coating layer on its surface; The coating layer is formed of carbon and zirconium nitride; In the lithium manganese iron phosphate material, the molar ratio of Li:Mn:Fe:P is (1-1.03):x:(1-x):1, where x takes a value of 0.5-0.7; The lithium manganese iron phosphate material is also doped with aluminum ions; The molar ratio of zirconium ions to nitrogen ions in the zirconium nitride is 1:(1-2). The molar ratio of zirconium ions to iron ions in the lithium manganese iron phosphate composite material is (0.001-0.005):1; The molar ratio of aluminum ions to manganese ions in the lithium manganese iron phosphate composite material is (0.001-0.005):1; The carbon content in the lithium manganese iron phosphate composite material is 1.2-1.4%; The preparation method of the lithium manganese iron phosphate composite material includes the following steps: S1. Iron source, phosphorus source, lithium source, manganese source, aluminum-containing additive A, carbon source and deionized water are mixed to obtain slurry A, which is then sintered to obtain carbon-coated lithium manganese iron phosphate sample A. The sintering procedure is as follows: first, heat to 200-250℃, then heat to 400-500℃, and sinter for 3-5 hours; the heating rate is 3-5℃ / min. S2. Mix the lithium manganese iron phosphate sample A, deionized water, soluble zirconium-containing additive B, soluble nitrogen-containing additive C, and carbon source to obtain slurry B; S3. Spray dry the slurry B under grinding conditions and sinter it to obtain the lithium manganese iron phosphate composite material. The sintering procedure is as follows: first, heat to 300-350℃, then heat to 750-780℃, sintering time is 6-8 hours, and heating rate is 3-5℃ / min.
2. The lithium manganese iron phosphate composite material according to claim 1, characterized in that: The particle size D of the lithium manganese iron phosphate composite material 50 The range is 0.8-1.5 μm, D 100 ≤7μm.
3. The preparation method of the lithium manganese iron phosphate composite material according to claim 1 or 2, comprising the following steps: S1. Iron source, phosphorus source, lithium source, manganese source, aluminum-containing additive A, carbon source and deionized water are mixed to obtain slurry A, which is then sintered to obtain carbon-coated lithium manganese iron phosphate sample A. The sintering procedure is as follows: first, heat to 200-250℃, then heat to 400-500℃, and sinter for 3-5 hours; the heating rate is 3-5℃ / min. S2. Mix the lithium manganese iron phosphate sample A, deionized water, soluble zirconium-containing additive B, soluble nitrogen-containing additive C, and carbon source to obtain slurry B; S3. Spray dry the slurry B under grinding conditions and sinter it to obtain the lithium manganese iron phosphate composite material. The sintering procedure is as follows: first, heat to 300-350℃, then heat to 750-780℃, sintering time is 6-8 hours, and heating rate is 3-5℃ / min.
4. The method for preparing the lithium manganese iron phosphate composite material according to claim 3, characterized in that: In step S1, the iron source is one or more of iron oxide, iron nitrate, and iron phosphate; The phosphorus source is one or more of ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and iron phosphate. The lithium source is one or more of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate. The manganese source is one or more of manganese trioxide, manganese tetroxide, and manganese carbonate; The aluminum-containing additive A is one or more of aluminum oxide, aluminum nitrate and aluminum carbonate; The carbon source is one or more of glucose, starch, and polyethylene glycol-1500.
5. The method for preparing the lithium manganese iron phosphate composite material according to claim 3 or 4, characterized in that: In step S1, the slurry A is wet-milled, spray-dried, and sintered to obtain the carbon-coated lithium manganese iron phosphate A sample; The slurry A is wet-milled to a particle size D. 50 It is 0.5-0.6μm; The conditions for spray drying are: inlet air temperature of 200-260℃ and outlet air temperature of 100-110℃.
6. The method for preparing the lithium manganese iron phosphate composite material according to claim 3 or 4, characterized in that: In step S2: The soluble zirconium-containing additive B is zirconium tetrachloride or zirconium nitrate; The soluble nitrogen-containing additive C is urea or ammonia.
7. The method for preparing the lithium manganese iron phosphate composite material according to claim 3 or 4, characterized in that: In step S3, the slurry B is ground to a particle size of 0.5-0.6 μm; The conditions for spray drying are as follows: The inlet air temperature is 200-260℃, and the outlet air temperature is 100-110℃.
8. A lithium-ion battery, comprising a positive electrode and a negative electrode; wherein the material of the positive electrode is the lithium manganese iron phosphate composite material as described in claim 1 or 2.
Citation Information
Patent Citations
Zirconium-containing lithium ion battery anode material and preparation method thereof and lithium ion battery
CN108807913A
Lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery
CN118919700A
Transition metal nitride and amorphous carbon composite coated and modified lithium manganese iron phosphate composite material as well as preparation method and application thereof
CN119100353A